Sustaining an Effective ABC-ABM System - Gary COKINS (Theoretical and Applied Economics, 2011)

(untitled)
The purpose of this paper is to describe the Activity- Based Costing (ABC) and Activity-Based Management (ABM) system and techniques to sustain them as a permanent and repeatable production reporting system, not just for one-off analysis. A comparison is made between ABC/ABM modeling software that extracts source data and business systems that include ABC/ABM modeling features. There are presented the stages of updating, running and rerunning the ABC/ABM system. The resulting information calculated and provided by the ABC/ABM system are analyzed and interpreted in terms of a multidimensional data analysis. The article ends with the authors’ conclusions about the benefits of continued operation of sustaining the ABC/ABM system.